Book Review: Radha Chakravarty, Novelist Tagore: Gender and Modernity in Selected Texts. (June 2015) - Gupta, Jayati
Radha Chakravarty, Novelist Tagore: Gender and Modernity in Selected Texts . New Delhi: Routledge, 2013, 160 pages, ₹ 595 (hardback), ISBN 978-0-415-8404